Neural activity in readiness for incidental and explicitly timed actions - Katharine S. Baker (2018)
Voluntary, self-initiated actions are preceded by slowly increasing neural activity in pre-motor regions of the brain, beginning up to 2. s before the onset of muscle movement. This activity is commonly seen in the scalp-recorded readiness potential, and is an index of movement preparation involving both motor programming and non-motor or cognitive processes such as attention. The specific contribution of cognitive processes, thought to occur during the earliest stage of planning, remains somewhat unclear. We suggest that attention to the timing of movement is a key voluntary process contributing to early-stage cortical activity. As a novel approach to examining this, we recorded EEG throughout a time reproduction task in which participants replicated the interval between two tones with two button-press actions. The first action, i.e. the beginning of the reproduced interval, was somewhat incidental to the task of time reproduction and required minimal attention to the time of initiation, while the second action required explicit attention to the time of initiation. Pre-movement neural activity preceding the first, relatively unattended movement was greatly reduced in amplitude and almost absent in the early stage, in contrast with readiness potentials typically seen prior to voluntary movement. Neural activity preceding explicitly timed movements was significantly larger, with effects emerging in the early component of pre-movement activity over frontal and right frontal scalp regions. We propose that attention to movement timing, i.e. the process of orienting attention in time towards the moment of movement initiation, is a key component of voluntary action preparation that is reflected in the early-stage neural activity we typically see prior to voluntary movement. © 2012 Elsevier Ltd.